Decontamination of radioactive wastewater : state of the art and challenges forward - Zhang, Xiaoyuan (2020)
Radioactive substances have been widely used in many industrial sectors, e.g. nuclear power station, biomedical engineering, etc. With increasing applications of nuclear technology, more and more radioactive wastewater is being generated via different channels, which indeed is posing an emerging challenge and threat to the environment and human health. Given such a situation, this review attempts to offer a holistic view with regard to the state of the art of technology for decontamination of radioactive wastewater as well as shed lights on the challenges forward. Different from reclamation of other types of wastewaters, the most challenging issue in decontamination of radioactive wastewater is the effective stabilization and solidification of soluble radioactive nuclides present in wastewater, which are critical for final disposal. Moreover, the potential risk of human exposure to wastewater radiation needs to be carefully assessed, and this issue should also be taken into consideration in the selection, design and operation of the radioactive wastewater treatment process. These clearly differentiate the treatment principle of radioactive wastewater from those of traditional industrial and municipal wastewaters. Lastly, the challenges from the perspectives of technology development, environmental and human health impacts and possible solutions forward are also elucidated.